2000
DOI: 10.1161/01.atv.20.7.1763
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Multimeric von Willebrand Factor Directs Sorting of P-Selectin

Abstract: Abstract-We designed a model system to study the role of von Willebrand factor (vWF) in the sorting of P-selectin and the biogenesis of Weibel-Palade body (WPB)-like organelles. For that purpose, a human epithelial cell line (T24) that synthesizes P-selectin mRNA, but which is devoid of vWF mRNA synthesis and storage organelles, was transfected with full-length vWF cDNA or a deletion mutant thereof. Stable transfectants of T24 with full-length vWF cDNA revealed the generation of WPB-like organelles as demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
0
28
3
Order By: Relevance
“…Hence, even though the mutation in the propeptide rendered the region incapable of its key chaperone function, it does not preclude interactions necessary for granular storage. While other studies have demonstrated multimerization of VWF to be necessary for granular storage, 37,38 our results demonstrate that VWF multimerization is not a prerequisite for storage. Rather, our model of VWF storage requires intact propeptide and structurally competent VWF that can associate noncovalently with VWFpp to cotraffick to storage granules.…”
Section: Discussioncontrasting
confidence: 87%
“…Hence, even though the mutation in the propeptide rendered the region incapable of its key chaperone function, it does not preclude interactions necessary for granular storage. While other studies have demonstrated multimerization of VWF to be necessary for granular storage, 37,38 our results demonstrate that VWF multimerization is not a prerequisite for storage. Rather, our model of VWF storage requires intact propeptide and structurally competent VWF that can associate noncovalently with VWFpp to cotraffick to storage granules.…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast, transfection of P-selectin cDNA leads to its storage in the endogenous granules of the transfected cell lines (28,29). Even though this result indicates that P-selectin contains an independent sorting signal now identified in the cytoplasmic tail (30), it also indicates that P-selectin needs some pre-existing storage granules to be directed to, as recently confirmed in transfected cells (31). Immunolocalization of P-selectin with the use of confocal microscopy showed that in resting vWf Ϫ͞Ϫ endothelial cells, P-selectin is found in a reduced number of small vesicles, compared with vWf ϩ͞ϩ cells (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…25,36 A similar degradation of P-selectin was demonstrated in the T24 human epithelial cell line that does not synthesize VWF. 29 We were unable to definitively identify the P-selectincontaining granules as lysosomes due to lack of availability of antibodies cross-reacting with canine lysosomal proteins. However, the degradation of P-selectin in the absence of a regulated secretory pathway is well-defined as previously described.…”
Section: Discussionmentioning
confidence: 97%